The effect of job stress on employees’ psychological strain - Feraidon Behzadi (New Applied Studies in Management, Economics & Accounting, 2022)
Currently employees are under a great stress such as excess, role doubt, role conflict, lack of feedback, and rapid technological change. This article aimed to determine the predictors of psychological strain and identify multidimensional criteria for psychological strain. The present study includes review research articles collected from Scopus and Science Direct databases. A total of 60 articles from 2015 to 2021 have been reviewed. This study is classified into components of work stress and psychological strain and then its definitions and dimensions are classified. It was observed that work stress affects different dimensions of psychological strain. These findings also indicate work-related stressors that can be classified into two main themes, which are work characteristics and psychosocial work characteristics. This article also helps to understand the conceptual knowledge of work stress, psychological strain and its causes and consequences in the workplace. Stress management workshops can be held regularly in different organizations in different departments, which can educate employees about the sources of stress and its harmful effects on health and how to reduce stress effectively. A total of 60 research articles on work-related stress and psychological consequences were reviewed in this study. In addition, the article is classified based on the main work stressors and dimensions of psychological strain in heterogeneous occupations.